A Water‐free Low Temperature Process for Atomic Layer Deposition of Al2O3 Films1. Issue 4 (16th May 2013) - Guo, Jiao‐Jiao; Li, Ming‐Da; Sun, Qing‐Qing; Yang, Wen; Zhou, Peng; Ding, Shi‐Jin; Zhang, David Wei; Knez, Mato; Yong, Qin
Abstract A new low temperature atomic layer deposition (LT‐ALD) Al2O3 process using trimethylaluminum (TMA) and acetic acid (CH3COOH) is studied both theoretically and experimentally. The atomistic mechanisms of the two deposition half‐cycles on Al‐CH3*, Al‐OH*, and Al(η2‐O2CCH3)* are investigated using density functional theory (DFT). The experimental demonstrations are performed on Si substrates over the growth temperature range 75–400°C. Consistent with the DFT simulation, lower linear growth rate and shorter required oxidant purge times are observed at 90°C, when compared to LT‐ALD Al2O3 using H2O as the oxidant. The chemical characteristics of the Al2O3 films grown with both CH3COOH at 90°C and H2O at 100°C are determined and compared using X‐ray photoelectron spectroscopy (XPS).